Complete Genome Sequence of Bacillus subtilis BSn5, an Endophytic Bacterium of Amorphophallus konjac with Antimicrobial Activity for the Plant Pathogen Erwinia carotovora subsp. carotovora - Deng, Yun (American Society for Microbiology, 2011)

(untitled)
Here, we present the complete genome sequence of Bacillus subtilis strain BSn5, isolated from Amorphophallus konjac calli tissue and showing strong inhibitory activity to Erwinia carotovora subsp. carotovora, which causes Amorphophallus soft rot disease and affects the industry development of this organism.